Physician-patient communication: elements for an ethical foundation. - Carrasco De Paula, Ignacio (Medicina e Morale, 2002)
The article dwells about the ethical aspects of the communication between the physician and his/her patient. The author introduces the matter with some observations of historicaldoctrinal nature (dialectics tradition/modernity) and continues specifically with a reflection on the ethical categories and conditions pertinent to a human activity, and therefore moral, as the communication between the physician and the patient. Particularly, the followings matters are treated: a. esteems and limits of the physician-patient communication in the traditional medicine (Corpus Hyppocraticum); b. the advent of technology in the modern medicine (conquests and traps); c. the ethical bases of the physician-patient communication in the clinical context.